Paradoxes in pediatric rehabilitation: building an interdisciplinary, total-child framework to promote effective interventions and life course well-being - Ramey, Sharon Landesman; Msall, Michael E.; Ramey, Craig T. (Frontiers in Pediatrics, 2025)
In this paper, we identify major paradoxes that have emerged from randomized controlled trials and longitudinal studies of diverse groups of young children with identified disabilities and risk conditions. We concentrate on the first three years of life because these coincide with a period of rapid changes in brain structure and function as well as dramatic expansion of a child's skills in motor, language, social-emotional, and cognitive domains. The paradoxes support a major revision in hypotheses about how effective interventions can alter a child's functioning and life course. The following conclusions derive from the paradoxes: (1) the intertwined biological and environmental influences on a child's well-being contribute more to functional outcomes than do the primary medical diagnoses and biological risks alone; (2) high-intensity, high-cost interventions that are well-timed, wholistic, and multi-domain can be more powerful and economical (i.e., yield higher “returns on investment”) than many treatments that initially appear less costly and easier to implement; (3) treatments that are individualized to the child and family, while adhering to evidence-backed treatment protocols, are among the most likely to result in large and long-lasting benefits compared to those that are solely individualized or adherent to a treatment protocol that does not make adjustments for the child; and 4) a clearly presented conceptual theoretical framework about human development can be a remarkably practical and informative tool in maximizing benefits of pediatric rehabilitation. We propose an interdisciplinary “total-child” platform – named the Interdisciplinary Monitoring, Planning, and Caring for the Total-Child – Together (IMPACT2) Developmental Framework - to support forming strong partnerships to facilitate informed clinical and family decision-making as well as the design and conduct of scientific investigations. We encourage others to consider these paradoxes and the IMPACT2 framework to stimulate conversations and promote innovative family and community partnerships to realize greater impact from delivering effective pediatric rehabilitation interventions to all eligible children.